Long, A. A. (2015). Greek Models of Mind and Self. Cambridge (MA), London, Harvard University Press (Revista Archai, 2016)
Resenha:Long, A. A. (2015). Greek Models of Mind and Self. Cambridge (MA), London, Harvard University Press